The Factors Contributing to Neonatal Sepsis at Yarsi Hospital and its Review From an Islamic Perspectiv - Lisda Suhani (Green Publisher Indonesia, 2026)
Neonatal sepsis remains one of the leading causes of morbidity and mortality in newborns and is influenced by various maternal, neonatal, and medical care–related factors. This study aimed to identify the risk factors associated with neonatal sepsis at YARSI Hospital and to analyze these factors from an Islamic perspective. This research employed an observational analytic design with a quantitative retrospective approach. Data were collected from secondary sources in the form of medical records of neonates diagnosed with neonatal sepsis who were treated at YARSI Hospital during the period of January 2022 to December 2024. The study population consisted of all neonatal sepsis patients during the study period, with samples selected using a total sampling method based on predetermined inclusion and exclusion criteria. Data analysis was conducted using univariate analysis to describe the distribution of variables and bivariate analysis using the chi-square test to examine the relationship between risk factors and the incidence of neonatal sepsis. The results showed that maternal factors, neonatal conditions at birth, and medical and environmental factors played an important role in the occurrence of neonatal sepsis. Early and appropriate management of neonatal sepsis is essential to reduce mortality, prevent complications, and improve neonatal outcomes. From an Islamic perspective, preventive and therapeutic efforts in neonatal sepsis align with the principles of maqāṣid al-sharī‘ah, particularly the protection of life (ḥifẓ al-nafs), lineage (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl).